Numerical Study Of Nanofluids Assisted Thermoelectric Air Conditioner - Saifuddin, Ahmad Syahir (IRC, 2020)
The effect of various type of nanofluids on thermoelectric cooling performance has been investigated numerically. This paper described the effect of nanofluids is used to assist the thermoelectric cooler for heat dissipation at the hot side to improve cooling performance the thermoelectric module. ANSYS Fluent is used to model and simulate the flow of nanofluids in minichannel Heat sink attached to the thermoelectric module hot side. The model described is validated with prior experimental study. The selected nanofluids are TiO2/water, Si02/water, TiO2/EG and Si02/EG, the volume concentration of nanoparticles for each nanofluids varies from 0.01%, 0.02% and 0.04%. The results of present work show that TiO2/water with 0.04% volume concentration as a coolant lead to highest COP of thermoelectric air conditioner. Numerical findings show that increase in volume concentration, improves thermal conductivity and thermal effectiveness between coolant and heatsink.